How Does the Social Support Influence Junior College Students’ Occupational Identity in Pre-school Education? - Huang, Jie; Qiao, Tianqi; Song, Zhanmei; Yan, Jingfeng (Frontiers in Psychology, 2022)
Objective: This study aimed to investigate the multiple mediating effects of achievement motivation and subjective well-being between social support and individual occupational identity. Methods: Questionnaire method was used in this study. 565 junior college students majoring in preschool education were tested by social support scale, achievement motivation scale, subjective well-being scale, and occupational identity scale. Results:(1) There isn’t significant relationship between perceptions of social support and individual occupational identity. (2) Achievement motivation and subjective well-being individually play a mediating role between social support and individual occupational identity. (3) Achievement motivation and subjective well-being play a chain mediating effect between elf-efficacy and individual occupational identity. Conclusion: Social support can indirectly predict professional identity of pre-school “would-be teachers” through the mediating effect of achievement motivation, subjective well-being and the chain mediating effect of achievement motivation and subjective well-being.